Language Teaching and Curricular Practices: A Comprehensive Literature Review - Melisa Rezi; Kddour Guettaoui Bedra (Lingeduca: Journal of Language and Education Studies, 2024)
Language teaching has evolved over the decades, driven by advancements in educational theories and the growing need for learners to communicate effectively in a globalized world. Curricular practices in language education have shifted from traditional grammar-based approaches to more communicative and task-oriented models. However, the implementation of these curricula varies across different contexts, raising questions about their effectiveness and adaptability. This comprehensive literature review aims to analyze the current trends, challenges, and best practices in language teaching and curriculum design. By synthesizing findings from empirical studies, the review examines how various curricular approaches impact language proficiency, learner engagement, and teaching methodologies. The study also explores the role of institutional support and teacher training in facilitating successful language education reforms. The review finds that communicative and task-based curricula significantly improve language proficiency and learner motivation. However, successful implementation requires adequate teacher preparation, appropriate resource allocation, and flexibility in curriculum design. Additionally, challenges such as cultural differences, institutional rigidity, and assessment practices can hinder the effectiveness of innovative curricular models. In conclusion, while communicative and task-based approaches show promise, their success is highly context-dependent. Future research should focus on developing adaptable curriculum models that accommodate diverse educational settings and explore long-term outcomes of these approaches.